STUDIES ON DIATOM DIVERSITY IN RESPONSE TO ABIOTIC FACTORS IN MAWATHA LAKE OF JAIPUR, RAJASTHAN: Life Sciences-Botany - SINGH, RAJESH; SINGH, MEENAKSHI; LODHA, PAYAL; PAL SINGH, GAJENDRA (International Journal of Life Science and Pharma Research, 2011)
The present investigation accounts on the diatom diversity, density and distribution in different seasons and their correlation with physico-chemical properties of water. The study period of 12 months duration from April 2009 to March 2010 revealed the presence of 30 diatom species. A limited number of these were recorded throughout the year, while others were distributed in different seasons mainly in winter and summer. These taxa belong to 19 genera viz. Stephanodiscus, Coscinodiscus, Cyclotella, Gomphonema, Melosira, Navicula, Hantzschia, Eunotia, Rhopalopodia, Cocconeis, Amphora, Synedra, Diatoma, Surirella, Fragillaria, Anomoeneis, Nitzschia, Diadesmis and Pinnularia. The deposited sediment samples of lake were found to be rich in sand (60%), silt (15%), clay (22%) and other soil nutrients as compared to control soil. Total diatom density showed significant positive correlation with electrical conductivity and total dissolved solids (p<0.01) and significant positive correlation with chemical oxygen demand (p<0.05). Shannon-Weiner diversity index (H’) value (1.372) and Evenness (J’) value (0.903) were found to be highest during winter while Berger-Parker index of dominance (0.147) was highest in monsoon. This study concludes that the diatom species attain maximum growth in post monsoon and winter months and gradually declines in summer to reach its minimum during monsoon.